Evaluation of the Effectiveness of Mobile Applications for Monitoring Blood Sugar in Type 2 Diabetes Sufferers - Djata, Dehen; Hoang, Nguyen Pham (Lembaga Publikasi Ilmiah Nusantara, 2025)
Background: The growing prevalence of Type 2 Diabetes (T2D) demands innovative approaches for self-management. In recent years, mobile health (mHealth) applications have emerged as practical tools for monitoring blood glucose, offering real-time data access, reminders, and personalized feedback. Objective: This article aims to evaluate the effectiveness of mobile applications in supporting blood sugar monitoring and management for individuals with T2D. Methods: This study employed a descriptive qualitative method using a literature review approach. Data collection involved academic document analysis sourced from Google Scholar, including scientific journals, books, and conference proceedings. Thematic content analysis was applied to identify key findings, patterns, and implementation strategies. Results: The study revealed that mobile applications facilitate improved glycemic control, better adherence to self-monitoring routines, and increased user engagement through real-time feedback and educational features. Key strategies include daily tracking, visual data representation, and personalized goal setting. These features positively impacted users’ motivation, health literacy, and decision-making autonomy. Conclusion: Mobile apps serve as effective mediators between clinical guidance and patient self-management. They foster a proactive health culture, empower patients, and enhance overall diabetes care outcomes.